The Anticancer Properties of Guava Leaves (Psidium guajava L.) and Turmeric Rhizome (Curcuma longa L.) Against Breast Cancer: A Literature Study - Angga Puja Asiandu; Widya Sari; Septi Widiya Sari; Alif Syahrul Abdul Majid (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Breast cancer, one of the most deadly diseases occurring in women, is caused by factors. In the healing process, the sufferer needs treatment, such as radiation techniques, surgery, and chemotherapy. But, these techniques have avoidable weaknesses that damage healthy cells. To date, natural sources can be utilized in medicine field. Guava (Psidium guajava L.) and turmeric (Curcuma longa L.) are two common plants obtaining compounds that inhibit the growth of cancer cells based on phytochemical properties. This study was written to review the potential both of plants as anticancer agents. Through the literature, guava leaf extract consists of flavonoids, tannins, alkaloids, saponins, terpenoids that inhibit the proliferation of cancer cells. Besides, turmeric also has tannins, alkaloids, terpenoids, flavonoids, glycosides, sterols, and curcumin. The presence of curcumin reduces histamine production which induce inflammation and decrease toxin. Because of curcumin, breast cancer cells have dehydration before apoptosis.